Finansowanie dziedzictwa kulturowego z funduszy UE - Madej, Sebastian; Madej, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The first part of the paper includes an outline of the history of funding of culture in Poland before and after its accession to the EU on the 1st May 2004. The main part of the article presents the results of a study among the recipients of the financial leverage available within measure 11.1. Protection and Maintenance of the Cultural Heritage of Superregional Importance of the Infrastructure and Environment Operational Programme. The authors discuss the results concerning the scale of funding for projects, as well as means of funding the beneficiaries’ contribution and difficulties involved. They also assess whether the achieved results are adequate to the expenses incurred
Keywords: finansowanie kultury; fundusze UE na kulturę; ochrona dziedzictwa kulturowego